Continuous Dual Resetting of the Immune Repertoire as a Basic Principle of the Immune System Function - Silvana Balzar (Journal of Immunology Research)
Idiopathic chronic inflammatory conditions (ICIC) such as allergy, asthma, chronic obstructive pulmonary disease, and various autoimmune conditions are a worldwide health problem. Understanding the pathogenesis of ICIC is essential for their successful therapy and prevention. However, efforts are hindered by the lack of comprehensive understanding of the human immune system function. In line with those efforts, described here is a concept of stochastic continuous dual resetting (CDR) of the immune repertoire as a basic principle that governs the function of immunity. The CDR functions as a consequence of system’s thermodynamically determined intrinsic tendency to acquire new states of inner equilibrium and equilibrium against the environment. Consequently, immune repertoire undergoes continuous dual (two-way) resetting: against the physiologic continuous changes of self and against the continuously changing environment. The CDR-based dynamic concept of immunity describes mechanisms of self-regulation, tolerance, and immunosenescence, and emphasizes the significance of immune system’s compartmentalization in the pathogenesis of ICIC. The CDR concept’s relative simplicity and concomitantly documented congruency with empirical, clinical, and experimental data suggest it may represent a plausible theoretical framework to better understand the human immune system function.